The Weight of Gratitude: Filipino Breadwinners’ Lived Experiences within The Context of Utang Na Loop - Rizaldy Lagmao Cabrera (Psikoislamika, 2025)
This study examines the lived experiences of Filipino breadwinners through the cultural lens of utang na loob (debt of gratitude), a core Filipino value signifying moral obligation and reciprocity. Using a qualitative phenomenological approach, the study explores how utang na loob influences the emotional, financial, and psychological well-being of Filipino breadwinners. Data were collected through semi-structured interviews with eight participants who identified as primary family providers. Findings reveal that breadwinners grapple with feelings of guilt, perpetual responsibility, and emotional exhaustion as they navigate the tensions between familial expectations and personal aspirations. Themes such as financial strain, intergenerational obligations, and the cycle of utang na loob highlight the dualities of pride and burden inherent in fulfilling familial roles. The study underscores the need to reassess familial expectations and support systems to balance individual well-being with familial obligations.